Increasing the efficiency of hot mandrel bending of pipe elbows. (2017) - Tabakajew, D.; Homberg, W.
Abstract: Hot forming, through pressing, forging or spinning, for example, is widely used in the metalworking industry. In small and medium-sized businesses, in particular, considerable potential exists for increasing productivity and efficiency in economic and ecological terms, because current production is often based on empirical experience and manual skills. Taking the example of pipe elbow production by the so-called 'Hamburg Process', new ways of optimizing the process chain are examined. Here, heated pipe sections are pushed over a horn-shaped mandrel, which defines the expansion and the radius of curvature. In this paper, the forming principle and technological process of hot mandrel bending of pipe elbows is presented. An analysis of the manufacturing process and the results of the first experimental investigations have shown that the production speed can be drastically increased without any negative effects on the quality of the pipe elbows. A further improvement in the output quantity and a substantial reduction in production costs are expected following the design and execution of the FEM simulation, which will accurately depict the manufacturing process and can thus be used for the constructive and structural design of the mandrels.